Retrospective Study of Vitreous Tap Technique Using Needle Aspiration for Management of Shallow Anterior Chamber during Phacoemulsification - Ashraf Ahmed Nossair; Wael Ahmed Ewais; Lamia Samy Ali (Journal of Ophthalmology)
Purpose. To evaluate the technique of vitreous tap using needle aspiration for management of anterior chamber shallowness during phacoemulsification. Methods. A retrospective study included 26 eyes of 17 patients who underwent phacoemulsification in which vitreous tap was performed using a 27-gauge needle attached to a 5 ml syringe, inserted 3.5 mm from the limbus to aspirate 0.2 ml of liquefied vitreous if a cohesive (OVD) failed to sufficiently deepen the anterior chamber. Results. Preoperative anterior chamber depth was 2.31 ± 0.26 mm, axial length was 21.7 ± 0.67 mm, lens thickness was 4.5 ± .19 mm, and cataract grade was 3.77 ± 1.4. Preoperative CDVA in LogMAR units was 0.98 ± 0.75. Coexisting angle closure glaucoma was present in 7 patients (26.92%) preoperatively. Vitreous needle tap was successful in vitreous removal on the first attempt in 26 eyes (100%). Postoperative follow-up period was 22.88 ± 10.24 (4–39) months. The final postoperative CDVA in LogMAR units was 0.07 ± 0.1, while the final postoperative IOP was 16.54 ± 1.45 mmHg. No complications related to vitreous tap were noted. Conclusion. Vitreous needle tap is a simple, cost-effective, and safe technique for management of shallow anterior chamber in phacoemulsification.